GOOD GOVERNANCE DAN REFORMASI BIROKRASI DI INDONESIA - Zuhro, R Siti (Jurnal Penelitian Politik, 2016)
With the downfall of Soeharto’s New Order regime the authoritarian nature of the bureaucratic system was exposed The implementation of new political laws since 1999 gave rise to an invigorated role for political parties and the implementation of a government regulation for a neutral bureaucracy resulted in its declining involvement in politics. A strong parliament and the increasing political awareness of bureaucrats have become a reality today. These changes have put paid to questions about the involvement of political parties and the influence of societal forces in the formation of policy The bureaucracy can no longer exist as it was in the New Order and in fact has responded to societal needs by adjusting to the new political climate Indonesian politics under the transition era takes on a wider significance for one of the main results has been the emergence of bureaucratic pluralism a more pluralistic political system that is more open to the influence of these societal forces Improvement in governance became possible however with the rise of the reformation since 1998 At this time the debate on governance in Indonesia began with a consideration of good governance The post Soeharto era was seen by reformists as a long awaited opportunity to improve government policy so that people would not only follow the government’s decisions but would also contribute to the decision making process Indonesian demanded more democratic governance that is more regular interaction between government and civil society and freer participation by the latter in government institutions. Keywords Governance policy democratization reformation good governance.